Offline Effects of Online Connecting: The Impact of Broadband Diffusion on Teen Fertility Decisions - Melanie Guldi; Chris M. Herbst (Institute for the Study of Labor (IZA), 2015)
Broadband (high-speed) internet access expanded rapidly from 1999 to 2007. This expansion is associated with higher economic growth and labor market activity. In this paper, we examine whether the rollout also affected the social connections teens make. Specifically, we look at the relationship between increased broadband access and teen fertility. We hypothesize that increasing access to high-speed internet can influence fertility decisions by changing the size of the market as well as increasing the information available to participants in the market. We seek to understand both the overall effect of broadband internet on teen fertility as well as the mechanisms underlying this effect. Our results suggest that increased broadband access explains at least thirteen percent of the decline in the teen birth rate between 1999 and 2007. Although we focus on social markets, this work contributes more broadly to an understanding of how new technology interacts with existing markets.
Keywords: J13; J18; 330; fertility; birth rates; broadband; new media